Ästhetiken in Kindheit und Jugend - (:unkn) unknown (transcript Verlag, 2017)
In childhood and youth, an engagement with aesthetic modes of representation and perception is of great importance. The significance of aesthetic positionings – for instance through the choice of clothing or accessories, through make-up or gadgets – can on the one hand be interpreted as signs of a successful commercialization of childhood and youth. On the other hand, however, they testify to the savvy with which children and teenagers make their daily world their own and develop their design aesthetics. In order to consider the related social conditions of aesthetics, economies, and inter-generational relationships, this transdisciplinary volume brings together a range of research perspectives on everyday aesthetics in childhood and youth.
Sozialisation im Spannungsfeld von Kreativität, Konsum und Distinktion
Keywords: Kindheit; Jugend; Konsum; Mode; Körper; Geschlecht; Medien; Kommunikation; Spiel; Kultur; Sozialisation; 305 Soziale Gruppen